Family Variables and Internet Fraud Tendency Among Undergraduates in Public Universities in Cross River State, Nigeria: A Literature Review Perspective - Joyce Boniface Bekeh (INTERNATIONAL JOURNAL OF EDUCATION AND EVALUATION, 2026)
It is apparent from the foregoing that family variables can determine the tendency to participate in internet fraud among undergraduates in universities in Cross River State. Despite the government's efforts to regulate internet activities and reduce the incidence of cyber fraud, this problem still persists, especially among university undergraduates. Internet fraud tendency is the disposition to defraud another person using online tools and platforms. It is practically obvious that students who develop an interest in online fraud pay less attention to their studies, spend more time in internet-related activities, develop a passion for getting rich quickly, abandon their learning activities, practice academic dishonesty, and have generally low grades in their courses. General theory of crime states that the tendency to criminal behaviour is a consequence of low self-control. Self-control develops early in a person’s life and that a lack of self-control occurs when parents do not adequately supervise their children, do not recognize deviant behaviour in their children, or do not respond appropriately. Based on the theoretical review, it was concluded that academic interest, academic motivation, academic self-efficacy, family type, family size, and parenting style have implications on the extent to which undergraduates in public universities exhibit tendency to participate in internet fraud. It was recommended that lecturers in public universities in Cross River State should be encouraged to design academic activities that can enhance students’ academic self-efficacy in the universities and reduce their willingness to perpetrate internet fraud. Management of the universities should develop guidance and counselling programmes that can help students especially those from polygamous families, to deal with their family problems. This will help them to concentrate on their learning activities as well as reduce their dispositions for internet fraud-related activities.